Finance, Investment and Macroeconomics: The Neoclassical and a Post Keynesian Solution. - Sweeney, Richard J.; Gordon, Myron J. (Journal of Finance, 1996)
This work advances a theory of finance and investment under uncertainty and risk aversion which resolves problems left unsolved by Keynes in a manner consistent with his work. Keynes established that both the short-run and long-run performance of a capitalist system depend upon investment, but he failed to arrive at an alternative to the neoclassical theory of investment. Professor Gordon demonstrates that the extension of neoclassical theory to deal with uncertainty and risk aversion is based upon a string of assumptions which are empirically false. The competitive stationary state, the foundation for the neoclassical theory of a capitalist system, is shown to be unfeasible because it results in a very high probability of bankruptcy at the micro level and the system's early collapse on the macro level. Capitalists seeking long term survival are shown to be subject to a growth imperative, to the pursuit of monopoly power, and to a concern for financial policy. Later sections of the book discuss the consequences of this behaviour for short-run fluctuations and the long-run development of capitalist systems. This book advanves a new theory of finance and investment which recognizes the problem of bankruptcy when the future is uncertain. It should be of use to both post-Keynesian and neoclassical economists as a significant contribution to economic understanding.